Onfido: a case study of a values-focused start-up - Kassai, Husayn (Henry Stewart Talks, 2017)
Blue and red ocean strategies, Critical mass ideas, Fear of failure, Persistence and flexibility, Leveraging achievements, Selecting a team, Company values and culture, Structure and hierarchy, Feedback and communication, Mission